Trial of Intravenous Immune Globulin in Dermatomyositis - Aggarwal, Rohit; Charles-Schoeman, Christina; Schessl, Joachim; Bata-Csörgő, Zsuzsanna; Dimachkie, Mazen M; Griger, Zoltan; Moiseev, Sergey; Oddis, Chester; Schiopu, Elena; Vencovský, Jiri; Beckmann, Irene; Clodi, Elisabeth; et al. (The New England journal of medicine, 2022)
BACKGROUND: Intravenous immune globulin (IVIG) for the treatment of dermatomyositis has not been extensively evaluated. METHODS: We conducted a randomized, placebo-controlled trial involving patients with active dermatomyositis. The patients were assigned in a 1:1 ratio to receive IVIG at a dose of 2.0 g per kilogram of body weight or placebo every 4 weeks for 16 weeks. The patients who received placebo and those without confirmed clinical deterioration while receiving IVIG could enter an open-label extension phase for another 24 weeks. The primary end point was a response, defined as a Total Improvement Score (TIS) of at least 20 (indicating at least minimal improvement) at week 16 and no confirmed deterioration up to week 16. The TIS is a weighted composite score reflecting the change in a core set of six measures of myositis activity over time; scores range from 0 to 100, with higher scores indicating greater improvement. Key secondary end points included at least moderate improvement (TIS ≥40) and major improvement (TIS ≥60), and change in score on the Cutaneous Dermatomyositis Disease Area and Severity Index. RESULTS: A total of 95 patients underwent randomization: 47 patients were assigned to the IVIG group, and 48 to the placebo group. At 16 weeks, 79% of the patients in the IVIG group (37 of 47) and 44% of those in the placebo group (21 of 48) had a TIS of at least 20 (difference, 35 percentage points; 95% confidence interval, 17 to 53; P<0.001). The results with respect to the secondary end points, including at least moderate improvement and major improvement, were generally in the same direction as the results of the primary end-point analysis, except for the change in creatine kinase level (an individual core measure of the TIS), which did not differ meaningfully between the two groups. Over 40 weeks, 282 treatment-related adverse events occurred in the IVIG group, including headache (in 42% of patients), pyrexia (in 19%), and nausea (in 16%). A total of 9 serious adverse events that were considered to be related to IVIG occurred, including 6 thromboembolic events. CONCLUSIONS: In this 16-week trial involving adults with dermatomyositis, the percentage of patients with a response of at least minimal improvement based on a composite score of disease activity was significantly greater among those who received IVIG than among those who received placebo. IVIG was associated with adverse events, including thromboembolism. (Funded by Octapharma Pharmazeutika; ProDERM ClinicalTrials.gov number, NCT02728752.).
Keywords: Immunoglobulins, Intravenous; Adult; dospělí; Humans; dermatomyozitida; intravenózní imunoglobuliny; Creatine Kinase; lidé; dvojitá slepá metoda; Dermatomyositis; kreatinkinasa; Double-Blind Method